2023
DOI: 10.1227/neu.0000000000002302
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Trends in the Neurosurgery Match During the COVID-19 Pandemic

Abstract: In the present article, the impact of the COVID-19 pandemic on geographical trends in the neurosurgery match in successfully matched applicants was analyzed. A cross-sectional analysis for the years from 2017 to 2021 was performed. Successful applicants' region, state, and medical school were compared with the location of their matched residency program. The number of applicants matching at a residency program within the same region or state as their home medical school or their own medical school was then eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…Similar trends were observed in dermatology and otolaryngology. 4 , 5 To the author's knowledge, only 1 study exists within neurosurgery, in which a study by Moya et al 7 recently revealed that neurosurgery residents were not more likely to match into the state or region as their home medical school. While the study arrived at the same conclusion as the present study, it used 5 years instead of 4, and within the matched 4-year study period before and after COVID-19, assessed 868 residents, 8% less than the present study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similar trends were observed in dermatology and otolaryngology. 4 , 5 To the author's knowledge, only 1 study exists within neurosurgery, in which a study by Moya et al 7 recently revealed that neurosurgery residents were not more likely to match into the state or region as their home medical school. While the study arrived at the same conclusion as the present study, it used 5 years instead of 4, and within the matched 4-year study period before and after COVID-19, assessed 868 residents, 8% less than the present study.…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to reliance on the more limited data from the National Resident Matching Program, whereas the present study derived data from the institutions themselves. Moya et al 7 also failed to assess geographic trends relative to undergraduate and hometown location. The present study found that while the geographic trend did not vary with respect to COVID-19 or time for undergraduate or hometown region, more residents in neurosurgery match in the same state or region relative to their medical school than either undergraduate school or hometown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations